(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This comprehensive research paper investigates the concept and implications of the Uniform Civil Code (UCC) in the Indian context. This paper tries to examine the basic essence of the Uniform Civil Code and what does it mean when we use the term UCC. This paper starts with an introduction of Uniform Civil Code in which it defines the concept of the Uniform Civil Code and also discusses about its origin. It briefly talks about the history of the Uniform Civil Code and then with a focus on constitutional provisions, socio-political dynamics, and legal ramifications, it explores the relationship between UCC and personal laws, analysing judicial precedents and discussing its impact on India’s diverse religious and caste landscape. In this part it discusses how the formation of UCC will affect the personal laws operating in the country. It further discusses the need or desire for the Uniform Civil Code under this part itself, that whether the Uniform Civil Code should be implemented or it still falls in the category “desirable.” and what are the pros and cons of the same. As we proceed further, this paper discusses about the relationship of the Uniform Civil Code with the Secularism and discusses how implementation of the Uniform Civil Code may cause danger to the integrity of the nation and how this will lead to the breakdown off the peace and harmony among the people.